Stents and surgical interventions in the palliation of gastric outlet obstruction: a systematic review - Minata, Mauricio Kazuyoshi; Bernardo, Wanderley Marques; Rocha, Rodrigo Silva de Paula; Morita, Flavio Hiroshi Ananias; Aquino, Julio Cesar Martins; Cheng, Spencer; Zilberstein, Bruno; Sakai, Paulo; de Moura, Eduardo Guimarães Hourneaux (Endoscopy International Open, 2016)
Background and study aims: Palliative treatment of gastric outlet obstruction can be done with surgical or endoscopic techniques. This systematic review aims to compare surgery and covered and uncovered stent treatments for gastric outlet obstruction (GOO).Patients and methods: Randomized clinical trials were identified in MEDLINE, Embase, Cochrane, LILACs, BVS, SCOPUS and CINAHL databases. Comparison of covered and uncovered stents included: technical success, clinical success, complications, obstruction, migration, bleeding, perforation, stent fracture and reintervention. The outcomes used to compare surgery and stents were technical success, complications, and reintervention. Patency rate could not be included because of lack of uniformity of the extracted data. Results: Eight studies were selected, 3 comparing surgery and stents and 5 comparing covered and uncovered stents.The meta-analysis of surgical and endoscopic stent treatment showed no difference in the technical success and overall number of complications. Stents had higher reintervention rates than surgery (RD: 0.26, 95 % CI [0.05, 0.47], NNH: 4). There is no significant difference in technical success, clinical success, complications, stent fractures, perforation, bleeding and the need for reintervention in the analyses of covered and uncovered stents. There is a higher migration rate in the covered stent therapy compared to uncovered self-expanding metallic stents (SEMS) in the palliation of malignant GOO (RD: 0.09, 95 % CI [0.04, 0.14], NNH: 11). Nevertheless, covered stents had lower obstruction rates (RD: – 0.21, 95 % CI [-0.27, – 0.15], NNT: 5).Conclusions: In the palliation of malignant GOO, covered SEMS had higher migration and lower obstruction rates when compared with uncovered stents. Surgery is associated with lower reintervention rates than stents.